2021
DOI: 10.1038/s41598-021-90633-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals key genes associated with pigmentation in radish (Raphanus sativus L.) skin and flesh

Abstract: Radish (Raphanus sativus) is an important vegetable worldwide that exhibits different flesh and skin colors. The anthocyanins responsible for the red and purple coloring in radishes possess nutritional value and pharmaceutical potential. To explore the structural and regulatory networks related to anthocyanin biosynthesis and identify key genes, we performed comparative transcriptome analyses of the skin and flesh of six colored radish accessions. The transcript profiles showed that each accession had a specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Achieving uniformity in radish breeding in terms of color, size, and yield is becoming increasingly crucial [71]. Radishes' esthetic appeal and health advantages are significantly influenced by color [72]. However, there is little study on the detection, characterization, and quantification of flavonoids in multicolor radish.…”
Section: Breeding Goalsmentioning
confidence: 99%
“…Achieving uniformity in radish breeding in terms of color, size, and yield is becoming increasingly crucial [71]. Radishes' esthetic appeal and health advantages are significantly influenced by color [72]. However, there is little study on the detection, characterization, and quantification of flavonoids in multicolor radish.…”
Section: Breeding Goalsmentioning
confidence: 99%
“…The uniformity of various colours, sizes and yields are the factors becoming a high-priority goal in radish breeding [24]. Radish has a wide variety of colours that affect its appearance and its nutritional quality [25]. However, the detection, identification and quantification of flavonoids in multicolour radish are rarely explored.…”
Section: Breeding Goalsmentioning
confidence: 99%
“…RNA-seq has been used to investigate the overall expression profile of plants under different stresses, revealing the signal transduction pathways involved in the resistance network [ 17 ]. There are many studies that revealed the effects of different treatments on vegetable growth and development, functional phytochemicals, and stress resistance, such as radish [ 18 ], cabbage [ 19 ], and purple broccoli [ 20 ].…”
Section: Introductionmentioning
confidence: 99%